Socialization of Forage Type Introduction and Silage Production for Livestock Farmers Morome Village, South Konawe Regency - Munadi, La Ode Muh. (Teras Kampus as a member of PT Palem Edukasi Nusantara, 2025)
The aim of this community service is to improve the knowledge and skills of farmers in Morome Village, South Konawe Regency, regarding the introduction of high-quality forage types and silage production techniques. The method used involved socialization and training with a practical approach on silage production from local forages and agricultural waste. The results showed that farmers successfully identified more nutritious forages, such as elephant grass (Pennisetum purpureum) and legumes, and were able to process these materials into silage that can be stored for an extended period. However, some challenges, such as limited facilities and a lack of understanding in managing silage quality, were still faced by some farmers. Nevertheless, the overall activity had a positive impact on improving livestock feed security and farm productivity. In conclusion, silage production training can be an effective solution to overcome the feed shortage during the dry season.